High-titre circulating tissue transglutaminase-2 antibodies predict small bowel villous atrophy, but decision cut-off limits must be locally validated. (9th April 2014) - Beltran, L; Koenig, M; Egner, W; Howard, M; Butt, A; Austin, M R; Patel, D; Sanderson, R R; Goubet, S; Saleh, F; Lavender, J; Stainer, E; et al.
Summary: Numerous studies suggest that high levels of circulating immunoglobulin (Ig)A tissue transglutaminase (TTG2) antibodies predict coeliac disease with high specificity. Accordingly, it has been suggested that duodenal biopsy may not be required routinely for diagnostic confirmation where quantitative serology identifies the presence of high antibody titres. However, defining a cut-off TTG2 threshold is problematic, as the multiple available assay methods are not harmonized and most studies have been focused on the paediatric population. Recent paediatric guidelines proposed a TTG2 antibody diagnostic cut-off at 10 × the upper limit of normal (ULN) for the method; however, concerns remain about errors of generalization, between both methods and laboratories. In this study, we used retrospective laboratory data to investigate the relationship between TTG2 antibody levels and Marsh 3 histology in the seropositive population of adults and children at a single centre. Among 202 seropositive patients with corresponding biopsies, it was possible to define a TTG2 antibody cut-off with 100% specificity for Marsh 3 histology, at just over 10 × ULN for the method. However, UK National External Quality Assurance Scheme returns during the study period showed a wide dispersion of results and poor consensus, both between methods and between laboratories using the same method. Our results support the view that high-titre TTG2 antibody levels have strong predictive value for villous atrophy in adults and children, but suggest that decision cut-offs to guide biopsy requirement will require local validation. TTG2 antibody assay harmonization is a priority, in order to meet the evolving requirements of laboratory users in this field.